A Study on Research-gap in present E-waste Management and an Intuitive App-based Solution - Kumar Shaw, Jacky; Mukherjee, Anuja (International Journal of Computer Sciences and Engineering, 2025)
Electronic waste (e-waste) refers to the disposal of broken or obsolete e-components. E-wastes may be valuable and recyclable. Most e-wastes requires special handling in their disposal. Due to the rapid advancement of technology, electronic products become trash after a very short span of use. Most electronic devices those are improperly thrown away to a landfill or sold to local rag pickers never get safely disposed of let alone being recycled. These e-wastes contain many harmful materials like lead, copper, zinc, and brass. Due to reprehensible disposal of e-waste, the recycling facility of metals or plastics gets lost and the hazardous element gets leaked in the environment. Hence E-waste is becoming a serious issue as it affects global resource repository, green environment, and sustainability index. This paper paves a path that how does e-waste recycling mechanism can be considered as a service system. The major reason for waste issues, going by our research, comes from the attitude of urban dwellers towards treating their electronic wastes. According to 2016 dictum, the producer has to bear the responsibility of taking back their products. The paper depicts this process starting from a collection of wasted components by recyclers and then recycling it or disposing of it in an eco-friendly manner. Our primary goal is to make this process easier and faster for the end users using an online mobile app. This is an implementation of Extended Producer Responsibility (EPR) where the producer has to be concerned about the product after it gets expired.